Novel therapies in clinical use for the management of hyperlipidaemia - C. Mettananda (Sri Lanka College of Internal Medicine, 2023)
Optimal control of low-density lipoprotein cholesterol (LDLc) is identified as a major target in reducing cardiovascular disease burden globally. However, existing lipid-lowering therapies have not been able to achieve LDLc targets even in developed countries. Therefore, novel therapies for the management of hyperlipidaemia are being trialled. Currently, there are three main groups of newer medicines; bempedoic acid, PCSK9 inhibitors and inclisiran, in addition to statins and ezetimibe in use for the management of hyperlipidaemia. This article aims to introduce these newer medicines and their clinical use in the treatment of hyperlipidaemia.